2009
DOI: 10.4012/dmj.28.185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hybridization on bond strength and adhesive interface after acid-base challenge using 4-META/MMA-TBB resin

Abstract: The purposes of this study were twofold, namely to evaluate: (1) the effect of hybridization on microtensile bond strength (μTBS) to dentin, and (2) the ultrastructure of the dentin-adhesive interface with 4-META/MMA-TBB resin after acid-base challenge. Dentin surfaces, which received no treatment (NT), 65% phosphoric acid (PA), or 10% citric acid-3% ferric chloride (10-3), were bonded with a 4-META/MMA-TBB resin. To evaluate dentin bond strength, μTBS test was performed at a crosshead speed of 1 mm/min. For u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 12 publications
2
37
0
3
Order By: Relevance
“…Surprisingly, the zone was not observed in acid-etching system 15) . The previous study also reported a similar phenomenon with 4-META/ MMA-TBB resin 16) . Inoue et al (2006) established a simple method of specimen preparation to characterize the ABRZ in human teeth.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Surprisingly, the zone was not observed in acid-etching system 15) . The previous study also reported a similar phenomenon with 4-META/ MMA-TBB resin 16) . Inoue et al (2006) established a simple method of specimen preparation to characterize the ABRZ in human teeth.…”
Section: Discussionsupporting
confidence: 52%
“…They demonstrated formation of an acid-base resistant zone (ABRZ) adjacent to the hybrid layer, which was influenced by adhesive material composition. The ABRZ was observed in the self-etching adhesive systems, but not in acid etching systems 15,16) . Shinohara et al reported that the thickness of the ABRZ was increased by fluoride ion release from the adhesive 1) .…”
Section: Introductionmentioning
confidence: 92%
“…A similar phenomenon was confirmed in the 4-META/MMA-TBB resin 15,16) . This study assessed the morphology of adhesive-dentin interface after acid-base challenge by scanning electron microscope (SEM) and transmission electron microscope (TEM) observation 13,14,17) .…”
Section: Introductionsupporting
confidence: 60%
“…ABRZ observation was performed according to the previous studies 15,17) . Each tooth was cut into two disks parallel and cutting surfaces were ground.…”
Section: Sem Observationmentioning
confidence: 99%
“…Sample preparation for SEM observation of dentin ABRZ was established by Inoue et al 7) and successfully applied in many studies afterwards [8][9][10][11][12][13]20) . However, considering the structural differences between dentin and enamel, it was necessary to seek optimal conditions for the acid-base challenge in order to observe enamel ABRZ.…”
Section: Discussionmentioning
confidence: 99%